Reproductive health crisis during waves one and two of the COVID-19 pandemic in India: incidence and deaths from severe maternal complications in more than 202,000 hospital births - Nair, M; Bharti, O; Bora, AK; Chhabra, S; Choudhury, SS; Choudhury, A; Das, B; Deka, G; Jain, P; Kakoty, SD; Kumar, P; Mahanta, P; et al. (Elsevier, 2021)
Background The SARS-CoV-2 pandemic in India has adversely affected many aspects of population health. We need detailed evidence of the impact on reproductive health in India so that lessons can be learnt. Methods Hospital-based repeated monthly survey of nine severe maternal complications and death in 15 hospitals across five states in India covering a total of 202,986 hospital births, December-2018 through to May-2021. We calculated incidence rates (with 95% confidence intervals (CIs)) per 1000 hospital births, case-fatality and rate ratios (RR) with 95% CIs. Linear regression was used to examine the association between the Government Response Stringency Index (GRSI) for India and changes in hospital births, incidence and case-fatality. Findings There was a significant decrease in hospital births per month during the pandemic period with a 4.8% decrease per 10% increase in the GRSI scores (p < 0.001). The overall incidence of severe complications in the pandemic period was not significantly different from the pre-pandemic period, but hospital admissions from septic abortion was 56% higher (RR=1.56; 95% CI=1.22–1.99; p < 0.001). The overall case-fatality of complications increased by 23% (RR=1.23; 95% CI=1.03–1.46; p = 0.022) and remained high across the different phases of the pandemic with a notable significant increase in deaths from heart failure in pregnancy. Interpretation Our study supports the legitimacy of the calls made to maintain sexual and reproductive health services as essential services during the pandemic. Lessons learnt should be used to avert the ongoing reproductive health crisis while India plans to manage a third wave of the pandemic. Funding The MaatHRI platform and this study are funded by a Medical Research Council Career Development Award to MN (Ref:MR/P022030/1). The funder has no role in the study design, data collection, analysis, or writing the paper